Sudden Unexpected Postnatal Collapse and Sudden Unexpected Infant Death. Issue 6 (November 2017) - Simpson, Kathleen Rice
Abstract : Current recommendations from the American Academy of Pediatrics and the Association of Women's Health, Obstetric, and Neonatal Nurses for continuous bedside attendance by nurses for mothers and babies during the recovery period and regular monitoring of mother-baby couplets during postpartum hospitalization are supported by numerous large case series reports of sudden unexpected postnatal collapse in the hospital setting.